Rectus sheath hematoma in post-lower segment caesarean section patient - Kamboj, Sunaina; Pal, Naresh; Arora, Bhavinder Kumar (International Surgery Journal, 2024)
Rectus sheath hematoma is a rather uncommon and often misdiagnosed clinical condition, usually follows abdominal trauma and anticoagulation. The daily activities of patient like sitting and lying in the bed produced the trauma which led to formation of hematoma. This trauma led to tear of inferior epigastric artery, which started bleeding with in the rectus sheath leading to formation of a big hematoma. Exploratory laparotomy was done. A hematoma of size 5×6 cm was visualized between anterior rectus sheath and rectus muscle on right side. Rectus muscle hematoma is due to shearing force to the inferior epigastric vessels due to routine activity of the patient.